Juventude universitária na modernidade religiosa : um estudo a partir do Instituto Luterano de Ensino Superior de Itumbiara-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The “Youth University in Religious Modernity Research: a study from the Instituto Luterano Superior de Itumbiara, GO”, focus on this study of a work with the purpose of understanding and academic investigation with young university students in city of Itumbiara, GO, specifically in this educational institution, but including young people from the south of Goiás and the Triângulo Mineiro. A sheds light on the conduct and understanding of the elements of the identity for young university students in late modernity religious, using orality expedients from the interview of ILES/ULBRA students, with an analysis and quality of the results. This work seeks to respond the lack of leading about this youth and their religious identities. ILES/ULBRA is a private education institution and it contains a very large diversity of young people, and it finds a propitious environment for this development, since there aren´t a great variety of beliefs, behaviors, ideas, ideologies, worldviews and identities. In this history of applicable importance as a perspective for the reorganization of religions in the modernity with religion´s authors and sociology of religion, as well as the sociology of youth.
Keywords: Juventude; Religiosidade; Modernidade; ILES/ULBRA; Sul Goiano; Triângulo Mineiro; Youth; Religiosity; Modernity; South of Goiás; FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO